Effect of Antimicrobial Agents Extracted from American Cockroach Insect Periplaneta Americana L. on Some Species of Microbes - Alaa Ali Hussein Al-Hindera1, Osama nadhom Nijris2, Husham Nagy Hamoudi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
current study was conducted for the period of October 2017 until November 2018 to investigate the effect of antimicrobial material of American cockroach Periplaneta americana hemolymph against strains of pathogenic bacteria and yeast. The samples of adults American cockroach was collected and divided into three major groups, the first collected their haemolymph without injecting the cockroaches with bacteria (non-immunizator) the second collected their haemolymph after 12 hours of being injected with E. coli (immunizator 12h), and the third group after 24 hours of being injected with the same bacteria (immunizator 24h), then divide each totals above to two subgroups one by cooling centrifuge on 4ºC and the other by table centrifuge at room temperature (non-cooling). protein concentration had measured of all transactions and was the highest value is immunizator 12-hour by cooling centrifuges.